Additional chemical polymerization of dual resin cements: reality or a goal to be achieved? - Luzia Sakaguti UMETSUBO; Karen Cristina Kazue YUI; Alessandra Bühler BORGES; Daphne Camara BARCELLOS; Sérgio Eduardo de Paiva GONÇALVES
Abstract Introduction This study serves as a warning to dentists and researchers that dual-cured resin cements may not polymerize completely under some prosthetic crowns. Objective The aim of this study was to analyse the polymerization degree of dual-cured resin cements under prosthetic barrier, by microhardness test. Material and method Three cements (Bistite II, RelyX ARC and Variolink II) were light-cured through different barriers, placed between the cement and the light source: G1: without barrier; G2: composite resin (Cesead); G3: Inceram alumina; G4: IPS Empress; G5: Inceram zirconia; G6: tooth fragment. Photopolymerization was carried out using a halogen light unit (650 mW/cm2); microhardness was evaluated using the Microhardness Tester FM 700, under a load of 50gf with a dwell time of 15s, at two evaluation times (30min and 24h). Result The results were submitted to ANOVA and Tukey tests (5%). Both Inceram alumina and Inceram zirconia ceramic barriers hindered polymerization. Bistite, followed by RelyX and Variolink, exhibited the highest microhardness values (p<0.05). As the highest values were obtained without a barrier, it was determined that the barrier, followed by the tooth, influenced microhardness. Both Empress and Cesead had the smallest microhardness values but with no statistically significant difference between them. Conclusion The barrier negatively affected the microhardness of dual-cured resin cements; evaluation time did not affect microhardness values for most of the conditions tested. There is a limited effect of the chemical activator on the polymerization of some dual-cured cements, and their performance is product specific.